IMPLEMENTASI SISTEM MONITORING DAN KONTROL AIR CONDITIONER MENGGUNAKAN INTERNET OF THINGS - Fritz Gamaliel; P. Yudi Dwi Arliyanto (Politeknik META Industri Cikarang, 2023)
Air conditioner is an electronic device for setting the room’ temperature which is controlled by a device from a short distance. The air conditioner is turned on when the room is in use, otherwise the air conditioner is turned off when the room is not in use. For turning on or turning off the air conditioner, the housekeeper must be in short distance to the air conditioner. There is moment when the housekeeper is not in short distance to the air conditioner but the air conditioner is turned on even though the room is not in use. The researcher overcomes this possibility by utilizing device control air conditioner from long distance based on internet of things. The device is Bardi On Off Breaker with maximum load 10 ampere. The device is installed on the air conditioner. The test results from this research is the housekeeper can monitor and control the air conditioner through a smartphone connected to the network internet without need short distance to the air conditioner